2005
DOI: 10.1124/mol.105.019364
|View full text |Cite
|
Sign up to set email alerts
|

Use of Penetrating Peptides Interacting with PP1/PP2A Proteins As a General Approach for a Drug Phosphatase Technology

Abstract: Protein phosphatase types 1 (PP1) and 2A (PP2A) represent two major families of serine/threonine protein phosphatases that have been implicated in the regulation of many cellular processes, including cell growth and apoptosis in mammalian cells. PP1 and PP2A proteins are composed of oligomeric complexes comprising a catalytic structure (PP1c or PP2AC) containing the enzymatic activity and at least one more interacting subunit. The binding of different subunits to a catalytic structure generates a broad variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 36 publications
3
49
0
4
Order By: Relevance
“…Ce résultat illustre bien un des prérequis de ces approches : les agents pharmacologiques doivent avoir une très haute affinité pour les sous-unités de PP2A qui sont ciblées, de façon à pouvoir contrecarrer efficacement la liaison à PP2A d'oncogènes cellulaires ou viraux. Dans ce contexte, nous avons proposé une approche thérapeu-tique appelée drug phosphatase technology, ou DPT, basée sur l'inhibition de processus pathologiques par transfert intracellulaire de peptides pénétrants mimant des sites d'interaction avec des protéines de la famille des protéine phosphatases PP1/PP2A (Figure 4) [28]. En particulier, nous avons caractérisé DPT-5, un peptide pénétrant contenant, à l'instar d'E4orF4, une séquence d'interaction (dans ce cas issue de l'antigène CD28) avec la sous-unité B de PP2A 1 , qui induit l'apoptose des cellules humaines [28].…”
Section: La Dérégulation De Pp2a Par Les Virus : Du Processus Tumoralunclassified
See 2 more Smart Citations
“…Ce résultat illustre bien un des prérequis de ces approches : les agents pharmacologiques doivent avoir une très haute affinité pour les sous-unités de PP2A qui sont ciblées, de façon à pouvoir contrecarrer efficacement la liaison à PP2A d'oncogènes cellulaires ou viraux. Dans ce contexte, nous avons proposé une approche thérapeu-tique appelée drug phosphatase technology, ou DPT, basée sur l'inhibition de processus pathologiques par transfert intracellulaire de peptides pénétrants mimant des sites d'interaction avec des protéines de la famille des protéine phosphatases PP1/PP2A (Figure 4) [28]. En particulier, nous avons caractérisé DPT-5, un peptide pénétrant contenant, à l'instar d'E4orF4, une séquence d'interaction (dans ce cas issue de l'antigène CD28) avec la sous-unité B de PP2A 1 , qui induit l'apoptose des cellules humaines [28].…”
Section: La Dérégulation De Pp2a Par Les Virus : Du Processus Tumoralunclassified
“…Dans ce contexte, nous avons proposé une approche thérapeu-tique appelée drug phosphatase technology, ou DPT, basée sur l'inhibition de processus pathologiques par transfert intracellulaire de peptides pénétrants mimant des sites d'interaction avec des protéines de la famille des protéine phosphatases PP1/PP2A (Figure 4) [28]. En particulier, nous avons caractérisé DPT-5, un peptide pénétrant contenant, à l'instar d'E4orF4, une séquence d'interaction (dans ce cas issue de l'antigène CD28) avec la sous-unité B de PP2A 1 , qui induit l'apoptose des cellules humaines [28]. Plus récemment, nous avons montré qu'un peptide DPT contenant un site de liaison de la protéine E4orf4 de chien qui interagit avec la sous-unité structurale B de PP2A 1 provoque l'apoptose des cellules tumorales humaines sans affecter les cellules saines (Galioot et al, en préparation).…”
Section: La Dérégulation De Pp2a Par Les Virus : Du Processus Tumoralunclassified
See 1 more Smart Citation
“…1, A-C). A recent study exploited cell-permeable peptides that mimic the structure of "phosphatase-interacting motifs" in specific subcellular targets of PP1 and PP2A; these peptides bind the phosphatase in the same manner as the substrate (Guergnon et al, 2006). The determination of phosphatase binding sites within a PP1 interacting protein (Bad) and a PP2A interacting protein (CD28) allowed for the construction of short corresponding peptides fused with a basic stretch of amino acids to confer cell permeability.…”
Section: Disrupting Phosphatase Complexes: Is It Possible?mentioning
confidence: 99%
“…While the main route of TP10 uptake is believed to be via the endocytic pathway (25), it has recently been suggested that perturbation of the lipid bilayer is required to maximize TP10 uptake (35). However, uptake does not necessarily translate into toxicity, as two newly designed CPPs are reported to accumulate in P. falciparum-infected red blood cells (RBCs) without killing the parasite but never enter noninfected RBCs (10). This may be related to the changes in erythrocyte membrane composition due to the formation of new permeability pathways (19).…”
mentioning
confidence: 99%